The Relationship Between the Level of Labor Fatigue and the Quality of Sleep in Fishermen - Darmawati, Siska; Lukman, Mamat; Koeryaman, Mira Trisyani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Work fatigue is a condition that can cause a decrease in efficiency as well as reduced strength or physical endurance of a worker's body and can affect the quality of sleep in workers. Fishermen have a high workload, irregular work schedules, which can affect fatigue and sleep quality. This study aims to determine the relationship between the level of work fatigue and the sleep quality of fishermen. The research method used is descriptive-correlative, using a cross sectional approach. The population in this study were all fishermen who actively worked in Karangjaladri Village, Parigi District, Pangandaran Regency, with a sample size of 131 fishermen. Data was obtained through the Job Fatigue Measuring Tool Questionnaire (KAUPK2) to measure the level of work fatigue and the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality in fishermen. The data analysis used to connect the two variables used the Spearman rank test. The results of the study showed that the level of work fatigue among fishermen in the less tired category was 19 fishermen (14.5%), 42 fishermen (32.1%) were tired, and 70 fishermen (53.4%) were very tired. The research results also showed that 21 fishermen (16%) had good sleep quality and 110 (84%) had poor sleep quality. The results of statistical tests show that there is a relationship between the level of work fatigue and the quality of sleep in fishermen, with a p value of 0.000. It can be concluded that fishermen have a level of work fatigue in the very tired category and have poor sleep quality.